Implementation of Character Education Through the Independent Curriculum to Face the Era of Society 5.0 - Asmawan, Moh. Chairil; Thoyibbah, Kartika; Gano-an, Jonathan Camana (Universitas Muhammadiyah Surakarta, 2023)
Education is a conscious effort to provide understanding in developing his life. The purpose of this study is to find out the application of character education implemented by SMKN 1 Banyudono through the independent curriculum and to find out the effectiveness and challenges of character education through the independent curriculum at SMKN 1 Banyudono. The method used is qualitative with a case study research design. The subjects of this study were the Vice Principal for Curriculum, the Vice Principal for Student Affairs, the P5 Supervising Teacher, and Students. The results showed that the character education activities or programs carried out included the application of employment, voice of democracy, local wisdom, implementation of religious Fridays, healthy Fridays, clean Fridays, zero plastic programs, intracurricular and extracurricular activities. The implementation of character education at SMKN 1 Banyudono through the independent curriculum has been running effectively, as evidenced by the student report cards that are above the SKL and from daily behavior, so that they are ready to face the era of society 5.0. The challenges faced in implementing character education are the internal conditions of students such as the state of problems experienced by students, laziness, and the influence of technology on the use of mobile phones.